Octylisothiazolinone, an additional cause of allergic contact dermatitis caused by leather: case series and potential implications for the study of cross‐reactivity with methylisothiazolinone. (November 2016) - Aerts, Olivier; Meert, Hans; Romaen, Elien; Leysen, Julie; Matthieu, Lucretia; Apers, Sandra; Lambert, Julien; Goossens, An
Summary: Background: Octylisothiazolinone (OIT) is used as an antifungal agent by the leather industry. Objectives: To show sensitization to OIT from leather, and to highlight the potential implications when cross‐reactivity between OIT and methylisothiazolinone (MI) is studied. Methods: Two patients with allergic contact dermatitis caused by a leather belt and shoes, respectively, were patch tested with methylchloroisothiazolinone (MCI)/MI, MI, MCI, OIT, and benzisothiazolinone (BIT). High‐performance liquid chromatography with ultraviolet detection (HPLC‐UV) was used to detect isothiazolinone derivatives in leather goods. Additionally, files of OIT‐sensitized patients, observed at the KU Leuven department during the period 1990–2015, were retrospectively analysed. Results: Both patients had been primarily sensitized to OIT, but the diagnosis in one of them could be achieved only when a higher patch test concentration of OIT (1000 ppm pet.) was used. HPLC‐UV confirmed the presence of OIT in their leather goods. Non‐relevant sensitization to MI was noted in both cases. Four additional cases of OIT sensitization from leather could be retrieved from the KU Leuven database. Conclusions: Non‐occupational sensitization to OIT from leather may occur. Patch test concentrations of >250 ppm pet. may be necessary for diagnosis, and to show cross‐reactivity with MI. Safer use limits for OIT in the leather industry may be needed.